First community-based post-COVID-19 cohort in northern Peru: protocol for bimodal assessment of pulmonary and psychological sequelae. The SUYAY TUMPIS Study - Rhor , Eva M. (2026)
The SARS-CoV-2 pandemic generated a significant burden of post-COVID-19 sequelae, including impaired pulmonary function and psychological morbidity. In Peru, community-level evidence on these sequelae remains scarce, particularly in rural settings. SUYAY TUMPIS is an observational open ambidirectional cohort study designed to determine pulmonary and psychological sequelae in COVID-19 survivors from urban and rural communities in the Tumbes region of northern Peru. A total of 270 adults (aged ≥18 years) with history of COVID-19 between 2020 and 2021 from Puerto Pizarro (rural) and AAHH Las Flores (peri-urban) will be enrolled, alongside 30 COVID-19-negative controls. Evaluations will be conducted at months 0, 6 (conditional), and 12. Pulmonary function will be assessed using portable spirometry (Datospir Aira-T: FVC, FEV1, FEV1/FVC, PEF) and non-contrast thoracic CT scan (SIEMENS SOMATOM GO, 16 slices) at baseline. Anxiety will be screened using the Generalized Anxiety Disorder-7 questionnaire (GAD-7) administered during home visits at months 0 and 12. Statistical analysis will include generalized linear models (Poisson family), survival analysis (Kaplan-Meier, Cox regression), and repeated-measures ANOVA. SUYAY TUMPIS is the first community-based post-COVID-19 cohort in northern Peru incorporating bimodal evaluation (pulmonary and psychological). Its findings will support evidence-based regional health planning.